Training for high-level performance in women's collegiate volleyball: Part II: Training program - Hedrick, A. (Strength and Conditioning Journal, 2008)
Based in part on the information provided in Part I of this article, the following training program for volleyball was developed. At the collegiate level, volleyball is a fall sport, with practice beginning in early August and competition running into November and December as teams advance into the post-season.